Issues and challenges of Islamic microfinance in post-conflict Somalia - Ali, Mohamed Abdikarim (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2020)
The institution of microfinance has been touted as a viable mechanism for poverty reduction in many parts of the developing world for several decades. Moreover, in post-conflict countries, microfinance is expected to play a larger role as an intervention tool for peace building, economic development, rebuilding institutional trust, reconciliation and restoring the lives and dignities of the poor and war-affected people. Somalia is in the wake of a conflict that has lasted for three decades, and the country urgently needs to institutionally rebuild the damaged economic and social infrastructures. A decade ago, the country witnessed the establishment of the first commercial banks that provide Shariah compliant services. The growing financial services, which are still considered a new phenomenon in the country, include microfinancing offered to the poor and low-income people. This research uses the Institutional Economic Theory (IE) and sets out to investigate the current situation of the emerging Islamic microfinance sector in post-conflict Somalia. the aim of the current study is to discover the issues and challenges facing Islamic microfinance and to chart the path forward to enhance and institutionalize the sector. The study designated to use the phenomenological methodology to form descriptive themes regarding the investigated phenomenon. The researcher conducted interviews with 15 respondents from the supply side who considered the key informants in the field of Islamic microfinance in Somalia. The in-depth face-to-face interviews provided rich data that was generated and refined using the NVIVO software. The study found that, although, the security situation in Somalia is still moving towards gaining full stability, the business environment in the country is thriving. The financial system of the country is found to be at the rebuilding stage, and all the 5 commercial banks are offering Islamic microfinance services based on qard-hasan and murabahah contracts to the low-income people, however, the capacity of the sector and coverage remains very small. Islamic microfinance programs and similar grants are confirmed to be the best intervention to support these war-affected people along with the utilization of zakah and waqf institutions. Moreover, the Islamic microfinance industry in Somalia faces many issues and challenges. The main challenge is the lack of microfinance regulations, lack of supportive environment, poor infrastructures, inadequate funding, low level of education and awareness and several issues related to engagement with the microfinance clients. Moreover, the study discovered several factors that can develop successful Islamic microfinance in Somalia. These factors include providing comprehensive such as savings, insurance and trainings to the low-income population in the country, increasing outreach and affordability and accessibility of Islamic microfinance services and these services should be at the heart of the Somali national policy agenda.